Analysis of Echocardiography Indicators Depending on the Type of Surgical Correction of the Mitral Valve in Patients with Ischemic Heart Disease - Volodymyr S. Moroz; Vasyl V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To study the influence of echocardiography indicators on the choice of surgical intervention on the mitral valve in patients with mitral insufficiency and coronary heart disease.Materials and methods. The study included patients with mitral insufficiency who underwent myocardial revascularization and mitral valve reconstruction (plasty or replacement). The mean age of the study participants was 65.9 ± 4.0 years. The material for analysis was data from the primary medical records: medical history, clinical and instrumental examination data and protocols of operations. The division into study groups was performed retrospectively, according to the mitral valve operation performed: plasty (experimental group) or replacement (control group).Results. We identified the features of the main echocardiographic data that guide the cardiologist when choosing the tactics of surgical correction of the mitral valve. It was established that in patients of the research group, the following was reliably significant: moderate degree of mitral insufficiency (p = 0.02; χ2 = 9.38), decrease in the systolic function of the left ventricle (p = 0.001; χ2 = 10.75); it was found that calcium deposits on the fibrous ring of the mitral valve were insignificant. When analyzing the morphological changes in patients of the experimental group, we found a significantly lower frequency of anterior leaflet prolapse (p = 0.04; χ2 = 4.21) and in general the frequency of all prolapses of any type, while in the control group the frequency of all prolapses was significantly higher (p = 0.04; χ2 = 4.0). In patients of the control group, a significantly higher frequency of akinesis (p = 0.04; χ2 = 4.21) and hypokinesis zones of the posterior-inferior-lateral wall (p = 0.001; χ2 = 19.76) was established, which is an additional sign of involvement of the chordal-muscular apparatus of the mitral valve in pathological process.Conclusions. As a result of the study, echocardiographic differences in the structure of the mitral valve were established, which influenced the selection of the intervention volume. It was found that in patients of the experimental group, the early postoperative mortality and the duration of inpatient treatment were significantly higher than in patients of the control group, which indicates the imperfection of the criteria used by cardiac surgeons when choosing the tactics of surgical correction of the mitral valve in an attempt to perform organ-preserving surgery.